Optimalisasi Penanganan Stockpile untuk Mencegah Terjadinya Swabakar pada Temporary Stockpile Batubara di PT. Lamindo Inter Multikon, Kabupaten Bulungan Kalimantan Timur - Wahyu Agung; Ika Arsi Anafiati; Ira Mughni Pratiwi; Warniningsih (Retii, 2022)
PT Lamindo Inter Multikon is a coal mining company located in the region Bunyu, North Kalimantan, Indonesia. Coal usually loaded by front-end into off-highway dump truck for transport to the stockpile before shipping to the market. Spontaneous combustion is one of the problems encountered during storage caused by storage times, recommended of coal pile dimension, and coal handling with First in First out (FIFO) method in temporary stockpile. Results and analysis of field research in pile dimensions as follows hopper (01+06) on chevcon pattern of stacking has 13.39 meters in height, angle of repose is about 40-68o, and hopper dimension (05+06) on pattern of cone ply stack has 14 meters in height, angle of repose 33o, this is exceeded its complement by 30o. On the stock hopper (01+06), the system and pattern of coal stacking in combination of chevcon and cone ply in line with FIFO rules. However, on the unloading process use Last in First out (LIFO), means that the most recent coal to come into the temporary stockpile should be sent out first. The new stock is used up first, taking priority over old stock. It leads to spontaneous combustion moreover less of coal temperature control in critical temperature at 50oC.